Document Clustering in the Age of Big Data: Incorporating Semantic Information for Improved Results - Haji, Saad Hikmat; Al-Zebari, Adel; Sengur, Abdulkadir; Kak, Shakir Fattah; Abdulkareem, Nasiba Mahdi (Interdisciplinary Publishing Academia, 2023)
There has been a meteoric rise in the total amount of digital texts as a direct result of the proliferation of internet access. As a direct result of this, document clustering has evolved into a crucial method that must be used in order to successfully extract relevant information from big document collections. When employing the document clustering approach, documents are automatically sorted into groups whose members have a high degree of similarity to one another. These groups are created by applying the document clustering technique. Because they do not take into account the semantic linkages that exist between the texts, traditional clustering approaches are unable to provide an acceptable description of a collection of texts. This is because traditional clustering techniques. Document clusters, in which texts are ordered according to their meaning rather than their use of keywords, have been extensively utilized as a means of overcoming these challenges as a result of the incorporation of semantic information. This has been possible as a result of the fact that document clusters can group together related texts. In this investigation, we looked at a total of 27 distinct papers that were published over the previous five years and categorized the documents based on the semantic similarities that existed between the various pieces. A detailed literature evaluation is included to each and every one of the publications that were selected for further consideration. Comparative research is carried out on a wide variety of evaluation strategies, including as algorithms, similarity metrics, instruments, and processes. Following that, there is a drawn-out discussion that analyzes the similarities and differences between the activities. © 2023, Interdisciplinary Publishing Academia. All rights reserved.
Keywords: Cloud computing; Document Clustering; Semantic Document Clustering; Semantic Similarity; WordNet